Domestic Violence Case Analysis At Regional Public Hospital Dr. Moewardi, Surakarta In 2018-2024 - Arrozhi, Muhammad Yusuf Arrozhi; Mahila, Niufti Ayu Dewi; Sulistio, Nadera Alia; Insani, Dinan; Dwi Atmoko, Wahyu (Universitas Ahmad Dahlan, 2025)
In Indonesia, the incidence of domestic violence has tended to increase over the past five years. There were 11,758 cases of domestic violence in 2018 and 16,519 cases in 2022. This study aims to determine the characteristics of cases in victims of domestic violence at Regional Public Hospital Dr. Moewardi Surakarta in 2018-2024. This study is a descriptive observational study using secondary data derived from medical records of victims of domestic violence at Regional Public Hospital Dr. Moewardi in 2018-2024. The sampling technique was done by total sampling. The research data was then analyzed for frequency distribution in the form of tables and graphs. There were 7 cases of domestic violence that occurred in the span of 2018 to 2024, the highest number of cases was in 2024, namely 4 cases, followed by 2022 with 2 cases and in 2021 with 1 case. In 2018, 2019, 2020 and 2023 there were no confirmed cases of domestic violence examined. The characteristics of the wounds on 50% of the victims were abrasions, 41.67% were bruises and 8.33% were cuts. The location of the wounds was 40% on the head, 26.6% on the upper extremities, 20% on the lower extremities, and 13.3% on the body. The highest incidence of domestic violence in the last 7 years was in 2024, all victims of domestic violence were adult women who suffered the most abrasions with the most wound locations on the head.